La protección del ambiente como límite al derecho de propiedad en Italia (2014)
In the attempt of protecting the environment, a number of specific limits to private property could be established. The constitutional principle of the “social function” of property enables the setting of a general limit to the possibilities of use the owner has over the asset, especially to the possibility the owner has of performing industrial immissions into the neighbor´s property. The purpose of this paper is to provide a hipothesis about the use of property to assure environmental protection. Everything is set in the context of the Italian civil code, chiefly what makes reference to real estate law and the Constitution of the Roman Republic.